Technical and Administrative Difficulties Facing Clubs of the Jordanian Women’s Professional Football League - Miqdadi, Mariam Emad; Abu-Shihab , Esam N. (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to identify the technical and administrative problems facing clubs of the Jordanian Women’s Professional Football League based on the variables of the club, years of experience, and educational qualification. Methods: The study utilized the descriptive survey method due to its relevance to the nature and objectives of the research. The non-random sample comprised 126 players from 7 teams participating in the Jordanian Women’s Professional Football League during the 2020/2021 season, as registered in the records of the Jordan Football Association clubs. Results: The study’s findings indicated that, on an overall level, the technical and administrative problems faced by clubs in the Jordanian Women’s Professional Football League were of a medium degree. Additionally, there were no statistically significant differences observed based on the study variables (club, years of experience, and educational qualification) concerning the problems encountered by clubs in the league. Conclusions: The study recommends the necessity of conducting specialized courses aimed at addressing the renewed technical and administrative challenges faced by players and the technical and administrative staff, in cooperation with sports clubs and institutions. This approach would help in overcoming the identified problems and difficulties more effectively.